Microstructural investigations on bonding mechanisms of cold-sprayed copper with SS316L steel. (2nd October 2020) - Singh, Surinder; Singh, Harpreet; Buddu, Ramesh Kumar
ABSTRACT: The purpose of the study was to understand the adhesion mechanism between cold-sprayed copper and SS316L steel substrate. Coatings of 3-mm thickness were deposited by cold-spraying on steel substrates prepared with different roughness values. To understand the bonding mechanism of the coating with substrates, scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) analyses were done on interfacial surfaces; exposed after the adhesion testing. Additionally, cross-sectional as-well-as top surface deformation behaviour of single copper particles deposited on steel substrates was investigated by using SEM/EDS, to elucidate the mechanism behind bonding. The results of the study validated that the adhesion is governed by both metallurgical bonding, as-well-as, mechanical interlocking, owing to the jetting formation. The mirror-polished surface resulted in a better adhesion strength as compared to the as-received and semi-polished surfaces, which was further validated by ultrasonic testing. Also, smaller-sized particles were found to be favourable for good adhesion strength.